PEMBERDAYAAN SISWA MELALUI PELATIHAN KEWIRAUSAHAAN KREATIF DAN PEMBUATAN PRODUK LOKAL - Muhamad Falahudin; Wildan Laksana; Idam Romadon; Siti Mariatus Shalihah; Nurhayati Nurhayati; Sudiharto Sudiharto (Yayasan Nusa Cendekia Global, 2026)
In an era of increasingly competitive globalization, the development of creative entrepreneurship and the ability to develop local businesses are important aspects for Vocational High School (SMK) students. This ability is needed to form superior entrepreneurial resources and be ready to compete in the business world. The effective application of creative entrepreneurship helps students to manage their time, determine priorities, and maintain motivation in undergoing the learning process and career preparation. In addition, local business development skills are the main provision in building confidence, communication, and the ability to make appropriate decisions in the work and social environment. This empowerment program aims to explore the application of creative entrepreneurship and the formation of local business development among students of SMK Mandiri 2 Balaraja, as well as analyze its impact on their readiness to enter the business world. The results of the study show that mastery of creative entrepreneurship and good local business development have a positive effect on the development of students' character, integrity, and adaptability in various work situations. The conclusion of this study emphasizes the importance of strengthening creative entrepreneurship skills, especially creative entrepreneurship and local business development, as part of the curriculum to create superior and competitive entrepreneurial resources at SMK Mandiri 2 Balaraja.